Chất vấn của các đại biểu Quốc hội về tiền tệ, ngân hàng tại phiên họp ngày 20/12/1991 - Phạm Văn Chi (1991)
Nội dung Chất vấn của các đại biểu Quốc hội về tiền tệ, ngân hàng tại phiên họp ngày 20/12/1991